Teacher Counselors’ Perception on the Impact of Guidance and Counseling Programs on the Satisfaction of Students’ Emotional Needs in Secondary Schools in Kenya - Ngeno , Godfrey; Shikuku , Mulambula (African Journal of Education,Science and Technology (AJEST), 2014)
An important role of guidance and counseling is to guide in the emotional development of the learner, facilitating healthy or positive emotions and discouraging negative emotions. Emotions play a key role in directing behavior of learners and shaping personality development. The school counselor is seen as a mentor and a guide in controlling emotional outbursts. The paper sought to find out the perception of teacher counselors on the impact of guidance and counseling programmes as currently implemented in schools on the satisfaction of students‟ emotional needs. The research study was guided by gestalt theory of perception. The target population for the study was all teacher counselors spread among secondary schools in five counties where ten secondary schools represented other schools which where selected through stratified random sampling method. Twenty teacher counselors were sampled and Ex. Post factor research design was adopted for the study. Data collection was done using questionnaires and the pilot study undertaken in three schools outside the sampled schools but within the same region and the reliability of the teachers questionnaire was 0.765. Expert opinion was sought to ascertain content and construct validity of the instrument. Data analysis was done using descriptive statistics. (Means) and inferential statistics (t – test and anova) used to test null hypothesis at 0.05 level of significance. The study found that the rigid schedules in secondary schools do not allow teacher counselors to attend to students‟ emotional needs. Teachers perceived that guidance and counseling has had positive impact on students‟ emotional needs satisfaction based on their overall means. The gender of teacher counselors, teaching experience, appointment criteria and counseling qualifications were found to influence their perceptions while school type, school category and age were insignificant. The paper recommends the strengthening of guidance and counseling programs to deal with gaps noted such as examination anxiety, sharing of emotional feelings, correction of students and coping with losses which have to be closed. In addition the following qualities of counselor were proposed such as friendly, comforter, considerate, role model, supportive, loving, persuasive, polite, sensitive, confidential, accommodating, eager and good listening in order to draw attention of the learners for counseling function in the area of emotional needs satisfaction